Language change the interplay of internal, external, and extra-linguistic factors - Jones, Mari C.; Esch, Edith (Contributions to the Sociology of Language [CSL], 2002)
This volume focuses on the interface of different motivating factors that contribute to language change. It combines linguistic case studies with current theoretical debate and contains hitherto unpublished data from English, French, Karaim, Modern Greek, Jordanian, Spanish, Latin and Arabic.
Keywords: Linguistic change; Languages in contact